2014
DOI: 10.1590/s1808-16572014000100008
|View full text |Cite
|
Sign up to set email alerts
|

Sorologia e suscetibilidade antimicrobiana em isolados de Escherichia coli de pesque-pagues

Abstract: RESUMO:Pesquisou-se a ocorrência de Escherichia coli (EPEC, EIEC, O157) em água e peixe (pele, trato digestivo e músculo) de pesque-pagues da microbacia do Córrego Rico, Jaboticabal (SP). Foram isoladas 115 cepas de E. coli, entre as quais 49 (43%) foram sorogrupadas como EPEC. Os sorogrupos mais frequentes foram O125, O126 e O158. Dentre as amostras testadas, 60 (52%) apresentaram resistência simultânea a dois antimicrobianos. A análise de correspondência foi realizada com o intuito de verificar as possíveis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
1
7
0
1
Order By: Relevance
“…Anthropogenic drivers of AMR included intensive and non-intensive (small-scale/extensive) animal production systems [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ] and agricultural practices [ 49 , 50 , 52 , 53 , 54 ], such as the use of recycled or composted animal or human manure as fertiliser. Resende et al [ 53 ] showed microbiological evidence of survival of AMR bacteria after biodigestion treatment of cattle manure, which could contaminate soils when applied as fertiliser.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Anthropogenic drivers of AMR included intensive and non-intensive (small-scale/extensive) animal production systems [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ] and agricultural practices [ 49 , 50 , 52 , 53 , 54 ], such as the use of recycled or composted animal or human manure as fertiliser. Resende et al [ 53 ] showed microbiological evidence of survival of AMR bacteria after biodigestion treatment of cattle manure, which could contaminate soils when applied as fertiliser.…”
Section: Resultsmentioning
confidence: 99%
“…Poultry was the most common livestock [ 35 , 37 , 39 , 42 , 43 , 44 , 45 , 49 , 50 , 52 ], but fish [ 36 , 48 ], swine [ 38 , 40 , 41 , 42 , 43 , 49 ], and cattle [ 41 , 42 , 46 , 49 , 51 ] were also studied. Only dos Vieira et al [ 47 ] focused on AMR in shrimp production.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Barbosa et al (21) identified 115 E. coli isolates, 19 were obtained from water, and 96 were obtained from fish. Regarding fish isolates, 26 were recovered from the skin, 65 from the gastrointestinal tract and five from the muscle.…”
Section: Resultsmentioning
confidence: 99%
“…Although uniform, the microbiota of fish can be influenced by physical, chemical, and biological conditions of water where they live. Thus, even though E. coli does not belong to the fish microbiota, it can be found or isolated due to the contamination of the aquatic environment in which the fish is produced (BARBOSA et al, 2014). RYU et al (2012), investigating the presence of E. coli resistant to antimicrobials in fish samples from South Korea, observed that approximately 40% of the isolates were resistant to tetracycline, streptomycin, cephalothin, ampicillin, tircacilin, sulfamethoxazole/trimethoprim, and nalidixic acid.…”
Section: Escherichia Colimentioning
confidence: 99%